Multicultural Education of Strengthening in Global Era Through Pancasila and Civics Educations (PPKN) Learning for Yunior High School Students Kartasura District - Suyahman Suyahman (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to describe the strengthening of multicultural education in theglobal era through PPKn Learning for Junior High School students in Kartasuradistrict. This research is qualitative research with descriptive approach.Research subjects: teachers, and students of class VII SMP Kartasura district,the object: multicultural education and PPKn Learning. Methods of datacollection: observation, interview and documentation. Validity of data is doneby triangulation of data and method. Data analysis technique is done by usinginteractive analysis technique consist of 3 stages: data reduction, data displayand data verification. The results showed: based on findings in the field that theexistence of multicultural education in SMP Kartasura district currently feltquite weak; this is indicated by the indicator: students form discussion groupstend to choose their friends who are in religion, students in terms of helping todistinguish the tribe, students in visiting his sick friends still consider thesimilarities of religion and tribe, students in performing art performance are stillsorting the same culture. Similarly, the results of interviews conducted onteachers, mentors, and students show that in general teachers, mentors, andstudents do not understand the meaning of multicultural, teachers and coachesfeel difficult to apply multicultural to students, students feel the lack ofexemplary attitude, behavior, and action teachers who reflect multiculturalvalues. The learning of PPKn can be used as a means of strengtheningmulticultural education in SMP Kartasura by: teacher appreciate and respect theexistence of different owned by every student either religion, tribe, culture, orlanguage different. Through PPKn Learning can be instilled in student studentsthe attitude of tolerance, mutual respect and mutual respect for the differencesof religion, ethnicity, culture, and language. Through Learning PPKN isimplanted in students to always live side by side despite the different religions,tribes, cultures, and languages peacefully and harmoniously. Through PPKNlearning can be educated to each student for mutual cooperation, mutualcooperation and public interest over personal and group interests by not lookingat differences in religion, ethnicity, culture and nation. Conclusion because ofthe weakness of the values of multicultural education for junior high schoolstudents Kartasura District, it is necessary to strengthen. One means ofstrengthening multicultural education can be done through PPKn Learning.Key Words: Multicultural Education and PPKn Learning